Construction of a Regression Test Automation System - Choi, Inhwa; Na, Wonshik (International Journal of Engineering and Technology, 2018)
Background/Objectives: As testing plays an important role in software quality assurance, many studies are now being carried out in areas such as test method design, test case generation, test case management, GUI test automation, and integrated test automation in order to create tests that are more efficient as well as cost efficient.Methods/Statistical analysis: This paper proposes a regression test automation system that can dynamically generate test cases in the regression test stage and automatically execute the generated test scenariosFindings: The Mocha framework is extended to build an automation framework, and test algorithms and test algorithms are classified to extend and combine various test cases.Improvements/Applications: Applying the proposed system to a UI development tool test saw more than twice the test cases being automatically generated, which led to a discovery of 37% more key defects.Â